HYGIENIC ANALYSIS OF NUTRITION AND FOOD QUALITY OF CHILDREN WITH OXALAT NEPHROPATHY IN PRESCHOOL AND SCHOOL AGE - Tajieva Zebo Baxodirovna; Shaykhova Guli Islamovna (Galaxy International Interdisciplinary Research Journal, 2021)
In recent years, the frequency of kidney diseases in children, including dysmetabolic nephropathy, has increased, which is associated both with improving the quality of diagnosis and the deterioration of the ecological situation. In this regard, the problem of early diagnosis,the appointment of adequate diet and drug therapy is relevant. The article deals with the problem of etiology, pathogenesis, as well as criteria for the diagnosis of dysmetabolic nephropathy in children. Attention is paid to the clinical manifestations of this pathology and the basic principles of treatment and prevention.